Integration of Sharia Economic Philosophy and Pancasila Economics: A Perspective for Indonesia - Suparman Kholil; Nurrohman Nurrohman; Yadi Janwari (CV. AFDIFAL MAJU BERKAH, 2025)
This study provides a conceptual and normative analysis of two significant economic systems in Indonesia: Islamic (Sharia) economics and Pancasila economics. Although they originate from different ideological foundations, both exhibit numerous similarities in their core principles, fundamental values, and goals. Islamic economics is based on Islamic teachings that emphasize justice, balance, and the prohibition of usury (riba), focusing on public welfare (maslahah) and equitable wealth distribution. Meanwhile, Pancasila economics is rooted in the values of Pancasila, particularly the fifth principle, which prioritizes social justice for all Indonesian people, emphasizing cooperation (gotong royong) and the balance between individual and societal interests. The analysis results indicate that both systems share common values in rejecting extreme individualism and materialism, focusing instead on collective welfare through fair wealth distribution. The fundamental difference lies in their ideological approaches: Islamic economics adheres to Islamic law (the Qur'an and Hadith) with specific rules such as the prohibition of usury and the obligation of zakat, while Pancasila economics is more flexible and adaptable to Indonesia's pluralism. The implementation of both systems in Indonesia shows a synergy, such as the development of Islamic banking and Sharia cooperatives, aligning with the principles of Pancasila economics. This study recommends strengthening this synergy through inclusive economic policies and broader education on the shared values between Islamic and Pancasila economics. In conclusion, despite their conceptual differences, Islamic economics and Pancasila economics have the potential to complement each other in achieving social justice and collective welfare in Indonesia.